Transformasi Digital dalam Pendidikan Indonesia: Analisis Kebijakan dan Implikasinya terhadap Kualitas Pembelajaran - Nashrullah, Mochamad; Syaiful Rahman; Abdul Majid; Nunuk Hariyati; Budiyanto (Prodi. Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat, 2025)
Digital transformation in education has become a strategic agenda to improve the quality and accessibility of learning in Indonesia. This study aims to analyze the policy of Directorate General of Teachers and Education Personnel Regulation No. 7607/B.B1/HK.03/2023, which focuses on technology-based performance management for teachers and school principals, and its implications for learning quality. The research employs the Literature Review method with data retrieved from Lens.org. The findings reveal that the policy provides a transparent and accountable framework; however, its implementation faces several challenges, such as gaps in technological infrastructure and digital literacy in remote areas. The policy's impact is more pronounced in urban areas with better access to technology compared to rural regions. This study recommends enhancing infrastructure, digital literacy training, and sustainable technical support to ensure the success of digital transformation in education. With inclusive and sustainable implementation, this policy has significant potential to improve educators' professionalism and learning quality.